After The Recent US Airline Mergers, Did Domestic Airfares Increase? - Barrows, Samuel D. (International Review of Management and Marketing, 2018)
The dynamics of the US domestic airfares are studied between 2002 and 2016. During this time frame, there was significant airline industry consolidations resulting in additional market concentration in the top four airlines and in the industry as a whole. The potential airfare increase resulting from this higher concentration is evaluated on both real and inflation adjusted bases through two cases. An analysis of load factors and passenger miles and their link with the airfare increases are also evaluated through two additional cases. A breakdown of all origin hubs in the US network is included which shows a vastly different airfare increase picture in the top twenty major hubs as compared to the smaller origins. Having healthy competition usually results in lower fares and this analysis confirms that dynamic. There are discussions on industry concentration, industry profitability, pricing power, and other items which can impact airfares. Keywords: Airline industry mergers, airfares increase, market power concentration JEL Classifications: L93, G34, R41